EMBRACING PROJECT-BASED LEARNING (PBL): A TRANSFORMATIVE METHODOLOGY FOR 21ST CENTURY EDUCATION - Jalolova Muqaddas; Toshtemirova Nilufarkhon Ashurali kizi (TADQIQOTLAR, 2025)
Abstract:  Project-Based  Learning  (PBL)  is  a  dynamic,  student-centered pedagogy that encourages learners to gain knowledge and skills by working over an extended  period  to  investigate  and  respond  to  authentic,  engaging,  and  complex questions,  problems,  or  challenges.  Unlike  traditional  methods,  PBL  fosters  deep learning, critical thinking, collaboration, and real-world application of knowledge. This article  explores  the  key  features,  benefits,  and  implementation  strategies  of  PBL, alongside its relevance in modern education. It also addresses the challenges educators face  while  adopting  this  approach  and  provides  recommendations  for  effective practice.